2019
DOI: 10.1186/s12967-019-02175-0
|View full text |Cite
|
Sign up to set email alerts
|

Lupus serum IgG induces microglia activation through Fc fragment dependent way and modulated by B-cell activating factor

Abstract: BackgroundNeuropsychiatric manifestations are frequent in patients with systemic lupus erythematosus (SLE), yet the etiology and pathogenesis of brain damage in SLE remains unclear. Because the production of autoantibodies, formation and deposition of immunocomplexes are major serological characteristics of SLE, the elevated level of serum immunoglobulin may contribute to brain tissue injury of SLE. To testify this, in this study, we examined whether immunoglobulin G (IgG) in the serum of SLE patients affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…Consistently, we and others found that IgG-induced neuronal cytolysis occurs in pediatric OMS rather than adult OMS [6,7]. Notably, increased microglial activation is not specific to only OMS, since previous literatures have documented that serum IgG from patients with PD [12] or ALS [13] enhances the activation of microglia and the production of NO, and serum IgG from patients with SLE induced behavioral changes are mediated by microglial activation [14][15][16]. Moreover, several autoantibodies found in patients with OMS [40][41][42][43] also exist in other diseases, such as autoantibody against glycine receptor in progressive encephalomyelitis with rigidity and myoclonus [42,44] or autoantibody against glutamic acid decarboxylase in stiff-person syndrome [44].…”
Section: Sera and The Igg Fraction From Children With Oms And Nb Givesupporting
confidence: 87%
See 2 more Smart Citations
“…Consistently, we and others found that IgG-induced neuronal cytolysis occurs in pediatric OMS rather than adult OMS [6,7]. Notably, increased microglial activation is not specific to only OMS, since previous literatures have documented that serum IgG from patients with PD [12] or ALS [13] enhances the activation of microglia and the production of NO, and serum IgG from patients with SLE induced behavioral changes are mediated by microglial activation [14][15][16]. Moreover, several autoantibodies found in patients with OMS [40][41][42][43] also exist in other diseases, such as autoantibody against glycine receptor in progressive encephalomyelitis with rigidity and myoclonus [42,44] or autoantibody against glutamic acid decarboxylase in stiff-person syndrome [44].…”
Section: Sera and The Igg Fraction From Children With Oms And Nb Givesupporting
confidence: 87%
“…The BCA assay (Pierce, Rockford, USA) was applied to determine IgG concentration. The Fab fragment of IgG was prepared by enzymatic digestion [16]. Pepsin (Sigma-Aldrich, St. Louis, MO, USA) was mixed with IgG at a ratio of 1:20, and then incubated at 37 °C for 6 h. Adjusting the solution pH to 7.4 to stop the digestion.…”
Section: Igg Purified From Sera and The Fab Fragment Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the expression of microglial marker soluble CD14 and proinflammatory cytokines is enhanced in CSF from patients with pediatric OMS [10,11]. Additionally, serum IgG from patients or autoantibody existed in patients directly enhances microglial activation in PD [12], ALS [13] and SLE [14][15][16], or initially binds with astrocytes or neurons and further indirectly affects microglial activation [43,44]. Autoantibodies are also detectable in sera and CSF of children with OMS [25,26] and may be contained in serum IgG from children with OMS and NB in our study, although we did not identify these autoantibodies and autoantibodies include IgM besides IgG.…”
Section: No/sgc/pkg Signaling Contributes To Conditioned Media-inducementioning
confidence: 99%
“…Notably, patients with pediatric OMS exhibit increased expression of a microglial marker and proinflammatory cytokines in cerebrospinal fluid (CSF) and some children with OMS are post-infectious [10,11]. Furthermore, serum IgG or autoantibody existed in patients enhances microglial activation in Parkinson disease (PD) [12], amyotrophic lateral sclerosis (ALS) [13] and systemic lupus erythematosus (SLE) [14][15][16]. Thus, it is reasonable to hypothesize that serum IgG from children with OMS and NB may impact the activation of microglia.…”
mentioning
confidence: 99%